Myenteric plexitis at the proximal resection margin is a predictive marker for surgical recurrence of ileocaecal Crohn's disease. (April 2015) - Misteli, H.; Koh, C. E.; Wang, L. M.; Mortensen, N. J.; George, B.; Guy, R.
Abstract: Aim: Identifying predictors for the recurrence of Crohn's disease (CD) after surgery to improve disease surveillance or targeted therapy is rational. The purpose of this study was to examine the relationship between myenteric plexitis (MP) and clinical or surgical recurrence. Method: Between 2000 and 2010, patients who underwent primary ileocaecal resection for CD at a single tertiary referral centre were identified. The histopathology was retrospectively reviewed for MP at the resection margins. The severity of MP was graded from 0 to 3 using a previously described classification. Information on demographics, surgical details and evidence of clinical or surgical recurrence was obtained from medical records. Results: There were 86 patients (49 women) of median age 31.5 (interquartile ratio 23.5–41.0) years. Seventy‐six and 77 specimens were assessable for proximal and distal MP. Proximal MP was present in 53 (69.7%) patients and was classified as mild, moderate or severe in 30 (39.5%), 14 (18.4) and nine (11.8%). MP at the distal resection margin was present in 40 (51.9%). Forty (46.5%) patients developed clinical recurrence of whom 16 (18.6%) required surgery. Clinical factors that predicted recurrence included age > 40 ( P = 0.001) and the presence of an anastomosis ( P = 0.023). On univariate analysis severe plexitis (Grade 3 MP) was also associated with surgical recurrence ( P = 0.035). Conclusion: This retrospective study supports the association between MP at the proximal resection margin and surgical recurrence.